INFLUENCE OF THE MAGNETIC FIELD ON FLOWING LIQUID OF SELECTED MAGNETIC PROPERTIES - Krawczyk, Mateusz; Skowron, Mikołaj (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
This paper presents the results of the effect studies of the magnetic field on the paramagnetic, flowing liquid. In the area of direct magnetic field the eddy currents in flowing liquid are induced. The induced currents affect the distribution of the magnetic field in the area where the liquid flows. The interaction of induced currents and magnetic fields affect changes in the direction of movement of the liquid and pressure changes in the liquid. The article presents the results of the calculations of the magnetic field, changes of the direction of flowing liquids, and pressure changes in the modelled liquid. Calculations were run in the Comsol Multiphysics.